2010
DOI: 10.4321/s0004-05922010000100013
|View full text |Cite
|
Sign up to set email alerts
|

Alimentação de leitoas pré-púberes com dietas contendo aflatoxinas ou zearalenona

Abstract: RESUMOUm experimento foi realizado para avaliar o desempenho, a morfologia vulvar e os pesos de órgãos viscerais e de trato reprodutivo em leitoas pré-púberes alimentadas com dietas contendo aflatoxinas ou zearalenona durante 28 dias. Foram utilizados 18 animais com peso médio inicial de 11 quilogramas. Três tratamentos (dieta controle -DC; DC + 1 mg kg -1 de aflatoxinas; DC + 2 mg kg SUMMARYAn experiment was carried out to evaluate performance, vulvae morphology, visceral organs and reproductive tract weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…Our results were corroborated by the study of Andretta et al (2010) and Teixeira et al (2011), who reported that ZEA do not significantly affect productivity of the animals.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results were corroborated by the study of Andretta et al (2010) and Teixeira et al (2011), who reported that ZEA do not significantly affect productivity of the animals.…”
Section: Discussionsupporting
confidence: 82%
“…They are responsible for considerable losses and adverse effects on animal health and production (Hauschild et al, 2007). Zearalenone (ZEA) is a non-steroidal estrogenic mycotoxin (Andretta et al, 2008;Andretta et al, 2010) …”
Section: Introductionmentioning
confidence: 99%
“…It has been found that at concentrations of 50-100 μg/kg in pig diet, ZEN affects oocyte implantation, ovulation, and fertilization. Similar changes were observed by Andretta et al (2010) and Teixeira et al (2011), who administered ZEN in an amount of 2 mg/kg BW and 0.75 mg/kg BW, respectively. Hyperemia and swelling of the vulva were observed in the first and third weeks of the experiment, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…ZEN was found to be toxic and carcinogenic. In gilts, experimental administration of ZEN or contaminated fodder at relatively low doses (from 1.5 to 2 ppm) leads to swelling and thickening of the vaginal and vulvar wall, increased uterus mass, and atrophic ovaries, but without the standing reflex (Andretta et al 2010). Rotter et al (1996) demonstrated that the animals most sensitive to DON are pigs.…”
Section: Discussionmentioning
confidence: 99%